On the validity of the Beck depression inventory: a review - Richter, Paul; Werner, Joachim; Heerlein Lobenstein, Andrés; Kraus, Alfred; Sauer, Heinrich (Psychopathology, 1998)
The present review discusses validity aspects of the Beck Depression Inventory (BDI) on the basis of meta-analyses of studies on the psychometric properties. Shortcomings of the BDI are its high item difficulty, lack of representative norms, and thus doubtful objectivity of interpretation, controversial factorial validity, instability of scores over short time intervals (over the course of 1 day), and poor discriminant validity against anxiety. Advantages of the inventory are its high internal consistency, high content validity, validity in differentiating between depressed and nondepressed subjects, sensitivity to change, and international propagation. The present paper outlines agreements and contradictions between the various studies on the BDI and discusses the potential factors (composition of the subject sample, statistical procedures, point in time of measurement) accounting for the variance in their results.